ATIM-03. TTFIELDS AND PULSED BEVACIZUMAB IN PATIENTS WITH BEVACIZUMAB-REFRACTORY RECURRENT GLIOBLASTOMA: A PHASE 2 STUDY. (5th November 2018) - Tran, David; Ghiaseddin, Ashley; Campian, Jian; Staal, Stephen; Warren, Sonisha; Allen, Anne; Sampson, Deborah; Greene, Valerie; Ansstas, George
Abstract: Despite aggressive treatment with surgery, radiation therapy and chemotherapy, the median overall survival for recurrent glioblastoma (rGBM) averages 25 weeks. Our prior experience in 8 bevacizumab-refractory GBM patients initially treated with TTFields monotherapy and re-challenged with bevacizumab on progression suggest that successive cycles of on/off (or pulsed) bevacizumab dosing will produce peaks and troughs in the mitotic activities of glioma cells that render these cells more sensitive to the antimitotic activity of TTFields during peak growth rates and may lower disease burden and increase survival. This Phase 2, single arm, open label study [NCT02663271] investigates if TTFields combined with pulsed bevacizumab increases overall survival in bevacizumab-refractory GBM compared to historical controls treated with continuous bevacizumab alone or in combination with standard chemotherapy. Twenty-five adults male or female patients with bevacizumab-refractory rGBM (WHO grade IV) aged 22 years, KPS>60 will undergo 12 months of planned continuous TTFields (200 KHz) (60–75% compliance goal; patients<60% compliance at Month 2 withdrawn) followed by pulsed bevacizumab (10 mg/kg IV/ 2 weeks) on further progression (RANO), with option of extending treatment to 24 months in patients not progressed and/or have adequate performance status at the 12-month mark. Pulsed bevacizumab dosing is defined by at least one cycle on and at least one cycle off. A cycle is defined as 8 weeks in length. Primary endpoint is overall survival between the groups. Secondary endpoints include adverse events, KPS, QoL (Mini-Mental Status Exam) and response rate (RANO). Largest hazard ratio (HR)<1 (or smallest median survival time >3.3 months) that can be detected at 80%, 90%, or 95% power and a 1-tailed significance level of 0.05, by sample size (N=20 to 36, or 10 to 18 months of accrual at 2 patients per month) and shape parameter k=1.50, 2.50. To date 3 patients have been enrolled.